Boosting carbon sequestration by using forage grass in tropical deep soil with no-tillage - dos Santos Ferreira, João Henrique [UNESP]; Portugal, José Roberto [UNESP]; Fróes, Matheus [UNESP]; Bossolani, João William [UNESP]; Calonego, Juliano Carlos [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP] (Elsevier, 2025)
Soil is a significant reservoir of carbon (C), and soil management can lead to C release or sequestration. This 15-year study investigated the impact of intercropping on C dynamics during two growing seasons (2021/2022 and 2022/2023) of a soybean–maize succession system under long-term no-tillage. The treatments involved different crops intercropped with maize: no intercropping (fallow); ruzigrass; sunn hemp; and sunn hemp plus ruzigrass. Compared to no intercropping, intercropping ruzigrass enhanced C sequestration, resulting in a positive C balance (0.72 and 0.16 Mg ha−1 in the first and second evaluated seasons, respectively) and an average increase in C stocks (1-m depth) per growing season of ∼50 Mg ha⁻¹ . Conventional soil C assessments conforming to Intergovernmental Panel on Climate Change (IPCC) standards (up to 0.3 m depth) underestimated the total C stock by ∼64.9 %, revealing that these standards may not be suitable for accurately determining soil C stocks in tropical regions, particularly in deeper soil layers. These findings highlight not only the benefits of ruzigrass intercropping, emphasizing the role of cover crops in C sequestration and climate change mitigation, but also the limitations of conventional soil C assessments.